Evaluation of anticholinesterase effect of some Epilobium species and quantification of hyperoside by HPLC - Karakaya, Songul; Suntar, Ipek; Aydin, Bilge; Dursunoglu, Benan; Gozcu, Sefa; Senol, Onur; Kadioglu, Yucel (Taylor & Francis Ltd, 2022)
This article presents the evaluation of anticholinesterase effects of aerial parts of Epilobium angustifolium, E. stevenii and E. hirsutum and isolated flavonoids from E. angustifolium, and quantification of the flavonoids by HPLC. Besides, the highest acetylcholinesterase inhibition was seen in the EtOAc sub-extracts of E. angustifolium and E. stevenii (36.51 +/- 1.88 and 39.89 +/- 3.09%, respectively), whereas EtOAc sub-extract of E. angustifolium had the best butyrylcholinesterase inhibition (62.09 +/- 1.98%). Hyperoside showed strong inhibition activity on both enzymes. The active EtOAc sub-extract of E. angustifolium was quantitatively analyzed for their content of hyperoside (quercetin-3-O-beta-D-galactoside) by HPLC. The content of hyperoside in EtOAc sub-extract of E. angustifolium was detected as 3.312%. The anatomical structures of the stem, leaf, sepal, petal, anther, and filament of E. angustifolium were investigated. The anatomical properties given in this study provide a description of E. angustifolium.
Keywords: Anatomy; anticholinesterase; Epilobium; hyperoside; Onagraceae